Media Pembelajaran Yang Digunakan Pada Model Pembelajaran Problem Based Learning (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The rapid flow of scientific and technological developments requires an increase in the quality of human resources. Education has a very important function in improving the quality of human resources. In order to find quality human resources, quality education is also needed. Improving the quality of education needs to be carried out continuously and continuously. One way to improve the quality of education is to improve the curriculum.